Scottish Education and Society since 1945 - Paterson, Lindsay (Edinburgh University Press, 2023)
Scotland developed a series of educational surveys between the late-1940s and the early-21st century that allow the country’s experience of education to be studied in systematic detail. No other country has an archive of this length and depth. The surveys include evidence on pupils’ curriculum, attainment, subjective experience of school, and destinations after leaving school, as well as details of their social characteristics and of the secondary schools which they attended. By linking also to archival evidence on the histories of schools, the book’s analysis investigates the interplay between deliberate policy and wider social change. The transformation of education in this period is accompanied by equally important economic restructuring which has led to unprecedented changes in the way that education relates to lifelong opportunity in the twenty-first century. The book investigates how these changes have underpinned Scotland’s civic values, and have contributed fundamentally to shaping the debate about the country’s constitutional future.